Pengembangan Media Pembelajaran Berbasis Website Pada Mata Pelajaran Dasar Teknik Elektronika untuk Meningkatkan Hasil Belajar Siswa Sekolah Menengah Kejuruan - Amelda Amartha; Bagus Dwicahyono; Endi Permata (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to enhance the academic performance of vocational high school students in the Basic Electronic Engineering course through the development of a valid, practical, and effective web- based learning platform. Employing a Research and Development (R&D) methodology, the research utilized the 4D instructional design model, which encompasses the Define, Design, Develop, and Disseminate phases. The research subjects comprised 29 tenth-grade students enrolled in the Electrical Power Installation Engineering vocational program. Data were gathered utilizing pre-test and post- test assessments, supplemented by expert validation and feasibility questionnaires. According to Aiken’s V index calculations across material, construct, and linguistic aspects, the developed instrument demonstrated a remarkably high level of validity. Furthermore, evaluations conducted by subject-matter and media experts classified the product as